2017
DOI: 10.1002/kpm.1545
|View full text |Cite
|
Sign up to set email alerts
|

IT‐based clinical knowledge management in primary health care: A conceptual framework

Abstract: Primary health care medical practices have made sizable information technology investments in recent years, primarily deploying electronic medical record (EMR) systems as well as Web‐based e‐learning applications. The basic assumption here is that developing information technology‐based knowledge management capabilities may significantly improve the innovation and clinical performance of these organizations. Increasing uncertainty in their environment requires them to develop greater absorptive capacity (ACAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 128 publications
1
12
0
Order By: Relevance
“…The findings of the present study identified four challenges for health knowledge management in social media, including unwillingness of physicians and health organizations to interact with the public, endangering medical ethics by some nonspecialist users, patients' privacy, and negative patient comments. [ 41 42 43 44 45 ]…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the present study identified four challenges for health knowledge management in social media, including unwillingness of physicians and health organizations to interact with the public, endangering medical ethics by some nonspecialist users, patients' privacy, and negative patient comments. [ 41 42 43 44 45 ]…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, for sure our results confirm that a qualitative cognitive tool, as the Kahneman et al (2011) checklists, could potentially help physicians avoid these errors, but it needs to be integrated in daily practice, also as a more usable electronic version (Raymond et al 2017;Otokiti 2019). For sure this manuscript presents some limitations; most of them are those related to the use of the qualitative method which implies the interpretive role of researchers and limited extension of data.…”
Section: Discussionmentioning
confidence: 53%
“…With the exception of three publications (Paul, 2006; Cano et al , 2015; Raymond et al , 2017), the technology-focused papers investigate the introduction of a KM tool as a singular intervention.…”
Section: Resultsmentioning
confidence: 99%
“…All the technology-focused interventions increase the structural capital of the ambulatory healthcare provider by enhancing its IT infrastructure. The distance learning applications featured by Paul (2006) and Raymond et al (2017) also enhance human capital. IT-tools with communication functionalities (Paul, 2006; Chen et al , 2009) as well as patient-centered health trackers (Holbrook et al , 2009; Cano et al , 2015) enhance relational capital in addition to structural capital.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation